The effect of Audit Tenure, Audit Committee, and Audit Rotation on Audit Quality: Empirical Study of Manufacturing Companies in the Food and Beverage Sub Sektor in ISSI 2019-2023 - Sari, Quri Arifatma; Nurhidayat, Nurhidayat (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
The purpose of this study was to determine the effect of audit tenure, audit committee, and audit rotation on audit quality in food and beverage sub-sector manufacturing companies in the 2019-2023 ISSI. This research uses a quantitative descriptive approach with documentation methods. The sample for this research was 22 sample companies with 5 years of research which produced 110 data selected using the purposive sampling technique. The data analysis technique uses logistic regression analysis. The results find that audit tenure and audit rotation do not have a significant influence on audit quality, while audit committees have a significant influence on audit quality in food and beverage sub-sector manufacturing companies in the ISSI 2019-2023. Keywords: Audit Tenure; Audit Committee; Audit Rotation; Audit Quality; Food and Beverage Sector